2019
DOI: 10.30918/irjmms.72.19.022
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity analysis of etoposide and cisplatin on cell lines from human lung cancer and normal human lung

Abstract: Lung cancer is the leading cause of cancer-related deaths in the world with non-small cell lung cancer (NSCLC) making up a large majority of all cases. Despite advancement and discoveries in cancer therapy, treatment of this disease has been less successful due to serious side effects and drug resistance. Therefore, there is a need to research into new therapeutic approaches for this disease. This study, therefore, evaluated the effect of two common cytotoxic lung cancer drugs, the etoposide and cisplatin on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…It was also observed that free carboplatin exhibited no selective effect on cancer cells. Several studies have shown that platinum-based antineoplastic drugs, such as cisplatin and carboplatin which are commonly used in the clinical setting as chemotherapeutic agents in lung cancer treatment, have higher drug toxicity in healthy lung cells than lung cancer cells, and do not exert selective effects [9,26] which is in agreement with our study.…”
Section: In Vitro Cytotoxicity and Live/dead Staining Of Cellssupporting
confidence: 92%
“…It was also observed that free carboplatin exhibited no selective effect on cancer cells. Several studies have shown that platinum-based antineoplastic drugs, such as cisplatin and carboplatin which are commonly used in the clinical setting as chemotherapeutic agents in lung cancer treatment, have higher drug toxicity in healthy lung cells than lung cancer cells, and do not exert selective effects [9,26] which is in agreement with our study.…”
Section: In Vitro Cytotoxicity and Live/dead Staining Of Cellssupporting
confidence: 92%
“…For the other incubation points, in both assays, IC 50 were higher than the maximum concentration tested (32 µM) ( Table 1 ). The lower toxicity found for this complex towards non-tumor lung cells contrasts with the 7- to 13-fold higher toxicity profile reported for cisplatin against the same cell line (IC 50 values ranging from 2.4 to 4.15 µM, at 72 h) [ 37 , 38 , 39 ], which is a highly promising result regarding a potential future clinical application of [Pt 2 Put 2 (NH 3 ) 4 ] 4+ —a high anticancer activity coupled to a low toxicity against healthy cells being desired.…”
Section: Resultsmentioning
confidence: 96%
“…70,71 IC 50 values of cisplatin on BEAS-2B cells and their SI values for A549 and HeLa cells reported here are in good agreement with previous findings. [72][73][74] Among the Ir(III) complexes, the better values of the selectivity index (SI) were given by complex 2a-Cl in both tumoral A549 (3.30) and HeLa (2.23) cells, due to its higher cytotoxic activity in these cells (IC 50 3.73 and 5.53 in A549 and HeLa cells, respectively) compared to that in non-tumoral BEAS-2B cells (IC 50 12.32 µM). SI values for complex 2b-PF 6 and 3a-PF 6 were 1.90 and 0.73 (A549) and 0.69 and 0.47 (HeLa), respectively (Table 3), indicating low selective toxicity towards cancer cells.…”
Section: Biological Studiesmentioning
confidence: 99%